Solid catalyst component mixture for olefin polymerization, catalyst for olefin polymerization, and method for producing olefin polymer
By mixing the first olefin-based polymerization solid catalyst components of magnesium, titanium, halogen and succinic acid diester compounds with the second olefin-based polymerization solid catalyst components of magnesium, titanium, halogen and phthalate compounds in a predetermined proportion, the problem of difficult to take into account both the melt flowability and the flexural modulus of the olefin-based polymer in the prior art is solved, and polymer manufacturing with high melt flowability and high flexural modulus is achieved.
Patent Information
- Application Number
- CN202380055754.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-27
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to simultaneously improve the melt flowability and bending modulus of olefin-based polymers, especially when manufacturing polypropylene with a flexural modulus of 1900 MPa or more, the melt flowability is easily reduced.
The first solid catalyst component for polymerization of the first olefin-based polymerization containing magnesium, titanium, halogen and succinic acid diester compounds and the second solid catalyst component for polymerization containing magnesium, titanium, halogen and phthalate diester compounds are mixed in a predetermined ratio to form a solid catalyst component mixture for polymerization.
It is possible to manufacture an olefin-based polymer with a bending modulus of 1900 MPa or more without reducing the melt flowability, simplifying the manufacturing process and reducing energy costs and process counts.
Smart Images

Figure BDA0005254145090000091 
Figure BDA0005254145090000391 
Figure BDA0005254145090000392
Abstract
Description
Technical Field
[0001] The present invention relates to a solid catalyst component mixture for olefin polymerization, an olefin polymerization catalyst and a method for producing an olefin polymer. Background Art
[0002] In recent years, olefin polymers such as polypropylene (PP) have been used for various purposes such as containers and films in addition to molded products such as automobile parts and home appliances.
[0003] Polypropylene resin compositions are lightweight and excellent in moldability. Their molded products have excellent chemical stability such as heat resistance and chemical resistance. They are also very cost-effective and therefore are used in many fields as one of the most important plastic materials.
[0004] In order to further expand the application range, polypropylene having high melt fluidity (melt flow rate (MFR)), excellent moldability and excellent flexural modulus (FM) is desired, which can be used as a substitute for polystyrene and ABS resin.
[0005] In the polymerization of olefins such as propylene, there is known a polymerization method using a solid catalyst component containing a magnesium atom, a titanium atom, a halogen atom and an internal electron donating compound as essential components, and many methods have been proposed for polymerizing or copolymerizing olefins in the presence of an olefin polymerization catalyst containing the above-mentioned solid catalyst component, an organic aluminum compound and an organic silicon compound (see Patent Document 1, etc.).
[0006] For example, Patent Document 1 proposes a method for polymerizing propylene using a catalyst for olefin polymerization, wherein the catalyst for olefin polymerization comprises a solid titanium catalyst component loaded with an internal electron-donating compound such as phthalate, an organic aluminum compound as a co-catalyst component, and an organic silicon compound having at least one Si-OC bond. Many documents, including Patent Document 1, propose methods for obtaining a highly stereoregular polymer under high polymerization activity using phthalate as an internal electron-donating compound.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 57-63310
[0010] Patent Document 2: Japanese Patent Application Publication No. 2000-017019 Summary of the invention
[0011] Problem that the invention aims to solve
[0012] However, in recent years, there has been a demand for a solid catalyst component for olefin polymerization that can produce polypropylene having a flexural modulus (FM) superior to that of a solid catalyst component containing a phthalate ester as an internal electron donating compound, specifically a polypropylene having a flexural modulus (FM) of 1900 MPa or more.
[0013] The present inventors have conducted intensive studies to solve the above technical problems and have found that polypropylene having a high flexural modulus (FM) of 1900 MPa or more and excellent rigidity can be produced by using a solid catalyst component for olefin polymerization containing a succinic acid diester compound as an internal electron donating compound.
[0014] On the other hand, as described above, solid catalyst components for olefin polymerization are required to be components capable of producing olefin polymers having high flexural modulus (FM) and excellent rigidity, and having high melt fluidity (melt flow rate (MFR)) and excellent moldability.
[0015] However, in an olefin polymer obtained using an olefin polymerization catalyst (comprising an olefin polymerization solid catalyst component), melt fluidity (melt flow rate (MFR)) and flexural modulus (FM) are generally in a trade-off relationship.
[0016] Even when a polypropylene having a flexural modulus (FM) of 1900 MPa or more is produced using a solid catalyst component for olefin polymerization containing the above-mentioned succinic diester compound as an internal electron donating compound, the melt fluidity (melt flow rate (MFR)) of the obtained polypropylene tends to be extremely reduced.
[0017] In order to obtain an olefin polymer having both high flexural modulus (FM) and melt fluidity (melt flow rate (MFR)), a method of mixing multiple olefin polymers can also be considered, that is, a method of separately producing an olefin polymer having high melt fluidity and an olefin polymer having high flexural modulus and then mixing them.
[0018] However, when mixing a plurality of olefin polymers, there is generally a tendency that polymers having greatly different physical properties are difficult to mix with each other. In addition, depending on the olefin polymers to be mixed, a special mixing device with excellent stirring power is required during mixing, or a large amount of energy cost is required, and the number of steps is increased. Therefore, there is a technical problem that it is difficult to simply produce olefin polymers having desired properties.
[0019] Thus, as a solid catalyst component for olefin polymerization, there has been no known component that can produce olefin polymers having a melt fluidity (melt flow rate (MFR)) as high as 80 to 120 g / 10 minutes, excellent moldability, and a flexural modulus (FM) of more than 1900 MPa and excellent rigidity.
[0020] Under such circumstances, an object of the present invention is to provide a technical means for easily producing an olefin polymer having both high melt fluidity and rigidity.
[0021] Solutions for solving problems
[0022] In order to solve the above-mentioned technical problems, the present inventors have repeatedly conducted intensive studies and found that the above-mentioned technical problems can be solved by using a solid catalyst component mixture for olefin polymerization obtained by mixing a first solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and a succinic acid diester compound with a second solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and a phthalic acid diester compound in a predetermined ratio. The present invention was completed based on this finding.
[0023] That is, the present invention provides:
[0024] (i) A mixture of solid catalyst components for olefin polymerization, characterized in that it comprises a first solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and a succinic acid diester compound and a second solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and a phthalic acid diester compound in a mass ratio of first solid catalyst component for olefin polymerization: second solid catalyst component for olefin polymerization = 37:63 to 87:13.
[0025] (ii) The solid catalyst component mixture for olefin polymerization according to (i) above, wherein the content of the succinic acid diester compound is 4.7 to 14.9% by mass in terms of solid content.
[0026] (iii) The solid catalyst component mixture for olefin polymerization according to (i) or (ii) above, wherein the content of the phthalic acid diester compound is 2.2 to 7.9% by mass in terms of solid content.
[0027] (iv) An olefin polymerization catalyst, characterized in that it contains:
[0028] (I) a mixture of solid catalyst components for olefin polymerization according to any one of (i) to (iii) above; and
[0029] (II) one or more organoaluminum compounds selected from the group consisting of compounds represented by the following general formula (1),
[0030] R 1 p AlQ 3-p (1)
[0031] (In formula (1), R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, p is 0 < p ≤ 3. When there are multiple Rs 1 , each R 1 is optionally the same as or different from each other. When there are multiple Qs, each Q is optionally the same as or different from each other.).
[0032] (v) The olefin polymerization catalyst according to the above (iv), which contains:
[0033] (I) A mixture of solid catalyst components for olefin polymerization described in any one of the above (i) to (iii);
[0034] (II) One or more organoaluminum compounds selected from the compounds represented by the following general formula (1); and
[0035] (III) An external electron donor compound,
[0036] R 1 p AlQ 3-p (1)
[0037] (In formula (1), R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, p is 0 < p ≤ 3. When there are multiple Rs 1 , each R 1 is optionally the same as or different from each other. When there are multiple Qs, each Q is optionally the same as or different from each other.).
[0038] (vi) A method for producing an olefin polymer, characterized in that the olefin is polymerized using the olefin polymerization catalyst described in the above (iv) or (v).
[0039] Effects of the Invention
[0040] According to the present invention, it is possible to provide a mixture of solid catalyst components for olefin polymerization that can easily produce an olefin polymer having both high melt fluidity and rigidity, and it is also possible to provide an olefin polymerization catalyst and a method for producing an olefin polymer. Brief Description of the Drawings
[0041] Figure 1 is a diagram for explaining a method for producing a measurement specimen for measuring the proportion of the oriented layer in the cross-section of an injection-molded plate of an olefin polymer.
[0042] Figure 2This is a diagram for explaining a method for preparing a measurement sample for measuring the ratio of an oriented layer in a cross section of an injection-molded plate of an olefin polymer.
[0043] Figure 3 It is a diagram for explaining a method of specifying the ratio of the alignment layer.
[0044] Figure 4 This figure shows a polarizing microscope image of a measurement sample prepared in order to measure the ratio of the oriented layer in the cross section of an injection-molded plate of an olefin polymer.
[0045] Figure 5 This figure shows a polarizing microscope image of a measurement sample prepared in order to measure the ratio of the oriented layer in the cross section of an injection-molded plate of an olefin polymer.
[0046] Figure 6 This figure shows a polarizing microscope image of a measurement sample prepared in order to measure the ratio of the oriented layer in the cross section of an injection-molded plate of an olefin polymer.
[0047] Figure 7 This figure shows a polarizing microscope image of a measurement sample prepared in order to measure the ratio of the oriented layer in the cross section of an injection-molded plate of an olefin polymer.
[0048] Figure 8 This figure shows a polarizing microscope image of a measurement sample prepared in order to measure the ratio of the oriented layer in the cross section of an injection-molded plate of an olefin polymer.
[0049] Fig. 9 This figure shows a polarizing microscope image of a measurement sample prepared in order to measure the ratio of the oriented layer in the cross section of an injection-molded plate of an olefin polymer.
[0050] Fig.10 This figure shows a polarizing microscope image of a measurement sample prepared in order to measure the ratio of the oriented layer in the cross section of an injection-molded plate of an olefin polymer. DETAILED DESCRIPTION
[0051] First, the solid catalyst component mixture for olefin polymerization of the present invention will be described.
[0052] The solid catalyst component mixture for olefin polymerization of the present invention is characterized in that it contains a first solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and a succinic acid diester compound and a second solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and a phthalic acid diester compound in a mass ratio of first solid catalyst component for olefin polymerization: second solid catalyst component for olefin polymerization = 37:63 to 87:13.
[0053] The solid catalyst component mixture for olefin polymerization of the present invention contains a first solid catalyst component for olefin polymerization.
[0054] Examples of the first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention include a contact reaction product obtained by bringing raw material components serving as supply sources of magnesium, titanium and halogen into contact with a succinic acid diester compound serving as an internal electron donor compound in an organic solvent and reacting them. Specifically, examples include a contact reaction product obtained by using a magnesium compound and a tetravalent titanium halide as raw material components serving as supply sources of magnesium, titanium and halogen and bringing these raw materials into contact with an internal electron donor compound containing a succinic acid diester compound.
[0055] Examples of the magnesium compound include one or more selected from dialkoxymagnesium, magnesium dihalide, and alkoxymagnesium halide.
[0056] Among the above-mentioned magnesium compounds, dialkoxymagnesium or magnesium dihalide is preferred, and specific examples include dimethoxymagnesium, diethoxymagnesium, dipropoxymagnesium, dibutoxymagnesium, ethoxymethoxymagnesium, ethoxypropoxymagnesium, butoxyethoxymagnesium, magnesium dichloride, magnesium dibromide, and magnesium diiodide. Diethoxymagnesium and magnesium dichloride are particularly preferred.
[0057] Among the above-mentioned magnesium compounds, dialkoxymagnesium can be obtained by reacting metallic magnesium with an alcohol in the presence of a halogen or a halogen-containing metal compound.
[0058] The above-mentioned dialkoxymagnesium is preferably in the form of particles or powders, and its shape may be irregular or spherical.
[0059] When spherical dialkoxymagnesium is used as the dialkoxymagnesium, a polymer powder having a better particle shape (more spherical) and a narrower particle size distribution is obtained, the handling operability of the polymer powder generated during the polymerization operation is improved, and the occurrence of clogging caused by fine powder contained in the generated polymer powder can be suppressed.
[0060] The spherical dialkoxymagnesium is not necessarily a true sphere, and an elliptical or potato-shaped dialkoxymagnesium may also be used.
[0061] The average particle size (average particle size D50) of the dialkoxymagnesium is preferably 1.0 to 200.0 μm, more preferably 5.0 to 150.0 μm. The average particle size D50 refers to the particle size at which the cumulative particle size in the volume cumulative particle size distribution is 50% when measured using a laser scattering diffraction particle size analyzer.
[0062] When the dialkoxymagnesium is spherical, the average particle size D50 is preferably 1.0 to 100.0 μm, more preferably 5.0 to 80.0 μm, and even more preferably 10.0 to 70.0 μm.
[0063] In addition, regarding the particle size distribution of dialkoxymagnesium, dialkoxymagnesium having less fine powder and coarse powder and narrow particle size distribution is preferred.
[0064] Specifically, when the dialkoxymagnesium is measured using a laser scattering diffraction particle size analyzer, the particles having a particle size of 5.0 μm or less are preferably 20% or less, and more preferably 10% or less. On the other hand, when the dialkoxymagnesium is measured using a laser scattering diffraction particle size analyzer, the particles having a particle size of 100.0 μm or more are preferably 20% or less, and more preferably 10% or less.
[0065] Furthermore, if the particle size distribution is represented by ln(D90 / D10), it is preferably 3 or less, and more preferably 2 or less. Here, D90 refers to the particle size at which the cumulative particle size in the volume cumulative particle size distribution is 90% when measured using a laser scattering diffraction particle size measuring machine. In addition, D10 refers to the particle size at which the cumulative particle size in the volume cumulative particle size distribution is 10% when measured using a laser scattering diffraction particle size measuring machine.
[0066] The method for producing the spherical dialkoxymagnesium is exemplified in, for example, Japanese Patent Application Laid-Open Nos. 62-51633, 3-74341, 4-368391, and 8-73388.
[0067] In the solid catalyst component for olefin polymerization of the present invention, the magnesium compound preferably has a specific surface area of 5 m 2 / g or more, more preferably 5 to 50 m 2 / g, more preferably 10 to 40 m 2 / g.
[0068] By using a magnesium compound having a specific surface area within the above range as the magnesium compound, a solid catalyst component for olefin polymerization having a desired specific surface area can be easily prepared.
[0069] It should be noted that in the present application document, the specific surface area of the magnesium compound refers to a value measured by the BET method. Specifically, the specific surface area of the magnesium compound refers to a value measured by the BET method (automatic measurement) in the presence of a mixed gas of nitrogen and helium using an Automatic Surface Area Analyzer HM model-1230 manufactured by Mountech after vacuum drying the measurement sample at 50°C for 2 hours.
[0070] The magnesium compound is preferably in the form of a solution or a suspension during the reaction. By using the magnesium compound in the form of a solution or a suspension, the reaction can be preferably carried out.
[0071] When the magnesium compound is solid, it can be dissolved in a solvent in which the magnesium compound is soluble to form a solution, or suspended in a solvent in which the magnesium compound is not soluble to form a magnesium compound suspension.
[0072] When the magnesium compound is liquid, it may be used as a solution of the magnesium compound as it is, or it may be further dissolved in a solvent capable of solubilizing the magnesium compound and used as a solution of the magnesium compound.
[0073] Examples of the compound capable of solubilizing a solid magnesium compound include at least one compound selected from the group consisting of alcohols, ethers and esters, preferably alcohols such as ethanol, propanol, butanol and 2-ethylhexanol, and particularly preferably 2-ethylhexanol.
[0074] On the other hand, examples of the medium that does not have the ability to dissolve the solid magnesium compound include one or more selected from saturated hydrocarbon solvents or unsaturated hydrocarbon solvents that do not dissolve the magnesium compound.
[0075] In the solid catalyst component for olefin polymerization constituting the olefin polymerization catalyst of the present invention, the tetravalent titanium halide as a raw material component serving as a supply source of titanium and halogen is not particularly limited, and examples thereof include one or more compounds selected from the group consisting of titanium halides or alkoxytitanium halides represented by the following general formula (2).
[0076] Ti(OR 2 ) r X 4-r (2)
[0077] (Where R 2 represents an alkyl group having 1 to 4 carbon atoms, X represents a halogen atom such as a chlorine atom, a bromine atom, an iodine atom, and r is 0≤r≤3. )
[0078] In the general formula (2), r is 0≤r≤3. Specifically, r may be 0, 1, 2 or 3.
[0079] Examples of the titanium halide represented by the general formula (2) include one or more titanium tetrahalides selected from titanium tetrachloride, titanium tetrabromide, titanium tetraiodide and the like.
[0080] In addition, examples of the alkoxy titanium halide represented by the general formula (2) include one or more selected from methoxytitanium trichloride, ethoxytitanium trichloride, propoxytitanium trichloride, n-butoxytitanium trichloride, dimethoxytitanium dichloride, diethoxytitanium dichloride, dipropoxytitanium dichloride, di-n-butoxytitanium dichloride, trimethoxytitanium chloride, triethoxytitanium chloride, tripropoxytitanium chloride, tri-n-butoxytitanium chloride, and the like.
[0081] The tetravalent titanium halide is preferably titanium tetrahalide, and more preferably titanium tetrachloride.
[0082] These titanium compounds may be used alone or in combination of two or more.
[0083] In the first solid catalyst component for olefin polymerization constituting the solid catalyst mixture for olefin polymerization of the present invention, examples of the succinic diester compound include one or more compounds selected from the group consisting of compounds represented by the following general formula (3).
[0084]
[0085] (Where R 3 and R 4 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, which may be the same or different from each other, and R 5 and R 6 is a linear or branched alkyl group having 2 to 4 carbon atoms, which may be the same or different from each other.
[0086] In the compound represented by the above general formula (3), R 3 and R 4 It is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and they may be the same as or different from each other.
[0087] R 3 or R 4 In the case of an alkyl group having 1 to 4 carbon atoms, specific examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, and an isobutyl group.
[0088] In the compound represented by the above general formula (3), R 5 and R 6 The linear or branched alkyl groups having 2 to 4 carbon atoms may be the same as or different from each other.
[0089] R 5 and R 6 In the case of a linear or branched alkyl group having 2 to 4 carbon atoms, specific examples thereof include an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, and an isobutyl group.
[0090] In the first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention, as the succinic diester compound, examples of the dialkyl succinate represented by the general formula (3) include one or more selected from the following dialkyl succinates:
[0091] Diethyl succinate, diethyl 2,3-dimethylsuccinate, diethyl 2,3-diethylsuccinate, diethyl 2,3-di-n-propylsuccinate, diethyl 2,3-diisopropylsuccinate, diethyl 2,3-di-n-butylsuccinate, diethyl 2,3-diisobutylsuccinate;
[0092] Di-n-propyl succinate, di-n-propyl 2,3-dimethylsuccinate, di-n-propyl 2,3-diethylsuccinate, di-n-propyl 2,3-di-n-propylsuccinate, di-n-propyl 2,3-diisopropylsuccinate, di-n-propyl 2,3-di-n-butylsuccinate, di-n-propyl 2,3-diisobutylsuccinate;
[0093] Diisopropyl succinate, diisopropyl 2,3-dimethylsuccinate, diisopropyl 2,3-diethylsuccinate, diisopropyl 2,3-di-n-propylsuccinate, diisopropyl 2,3-diisopropylsuccinate, diisopropyl 2,3-di-n-butylsuccinate, diisopropyl 2,3-diisobutylsuccinate;
[0094] Di-n-butyl succinate, di-n-butyl 2,3-dimethylsuccinate, di-n-butyl 2,3-diethylsuccinate, di-n-butyl 2,3-di-n-propylsuccinate, di-n-butyl 2,3-diisopropylsuccinate, di-n-butyl 2,3-di-n-butylsuccinate, di-n-butyl 2,3-diisobutylsuccinate;
[0095] Diisobutyl succinate, diisobutyl 2,3-dimethylsuccinate, diisobutyl 2,3-diethylsuccinate, diisobutyl 2,3-di-n-propylsuccinate, diisobutyl 2,3-diisopropylsuccinate, diisobutyl 2,3-di-n-butylsuccinate, diisobutyl 2,3-diisobutylsuccinate.
[0096] Among these dialkyl succinates, diethyl succinate, di-n-propyl succinate, di-n-butyl succinate, diisobutyl succinate, diethyl 2,3-di-n-propyl succinate, diethyl 2,3-diisopropyl succinate, di-n-propyl 2,3-di-n-propyl succinate, di-n-propyl 2,3-diisopropyl succinate, diisopropyl 2,3-di-n-propyl succinate, diisopropyl 2,3-diisopropyl succinate, di-n-butyl 2,3-di-n-propyl succinate, di-n-butyl 2,3-diisopropyl succinate, diisobutyl 2,3-di-n-propyl succinate, and diisobutyl 2,3-diisopropyl succinate are preferably used.
[0097] The first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention preferably contains 5 to 28 mass % of the succinic diester compound, more preferably 10 to 24 mass %, and even more preferably 15 to 20 mass %, expressed in mass % as solid content.
[0098] The first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention preferably contains a succinic diester compound in a molar percentage of 0.019 to 0.108 mole %, more preferably 0.039 to 0.093 mole %, and even more preferably 0.058 to 0.077 mole % in terms of solid content.
[0099] In the first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention, the ratio (D1 / T) of the content of the succinic diester compound (D1) to the content of titanium (T) is preferably 3.5 to 6.6 in terms of mass ratio, more preferably 4.1 to 6.0, and further preferably 4.8 to 5.4.
[0100] In the first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention, the ratio (D1 / T) of the content of the succinic diester compound (D1) to the content of titanium (T) is preferably 0.3 to 1.3 in terms of molar ratio, more preferably 0.5 to 1.2, and further preferably 0.7 to 1.1.
[0101] By making the content ratio of the succinic acid diester compound in the first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention, or the ratio (D1 / T) of the content ratio of the succinic acid diester compound (D1) to the content ratio of titanium (T) within the above-mentioned range, when provided for olefin polymerization, it is possible to easily produce olefin polymers having excellent melt fluidity and even better flexural modulus.
[0102] The first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention contains a succinic acid diester compound as an internal electron donor compound as an essential component, but in addition to these internal electron donor compounds, it may also contain other internal electron donor compounds (hereinafter appropriately referred to as "other internal electron donor compounds").
[0103] Examples of such other internal electron donating compounds include one or more selected from carbonates, acid halides, amides, nitriles, acid anhydrides, diether compounds, carboxylic acid esters and the like.
[0104] Specific examples of such other internal electron donating compounds include at least one selected from ether carbonate compounds, carboxylic acid diesters such as cycloalkane dicarboxylic acid diesters, cycloolefin dicarboxylic acid diesters, malonic acid diesters, alkyl-substituted malonic acid diesters, and maleic acid diesters, and diether compounds.
[0105] More specifically, more preferred is one or more selected from ether carbonate compounds such as (2-ethoxyethyl) methyl carbonate, (2-ethoxyethyl) ethyl carbonate, and (2-ethoxyethyl) phenyl carbonate, dialkylmalonate diesters such as dimethyl diisobutyl malonate and diethyl diisobutyl malonate, cycloalkane dicarboxylic acid diesters such as dimethyl cyclohexane-1,2-dicarboxylate, and 1,3-diethers such as (isopropyl) (isopentyl)-1,3-dimethoxypropane and 9,9-bis(methoxymethyl)fluorene.
[0106] On the other hand, in the first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention, the content ratio of the phthalic acid diester compound is appropriately 0.2 mass % or less (0.0 to 0.2 mass %), more appropriately 0.1 mass % or less (0.0 to 0.1 mass %), and further appropriately 0.0 mass % (substantially containing no phthalic acid diester compound (below the detection limit)).
[0107] In the present application document, the content ratio of the succinic acid diester compound contained in the solid catalyst component for olefin polymerization, the content ratio of other internal electron donor compounds added as needed, and the content ratio of the phthalic acid diester compound (described later) refer to the values obtained by measuring the solution of the solid catalyst component for olefin polymerization by a gas chromatography FID (Flame Ionization Detector) method after heating and drying the solid catalyst component for olefin polymerization under reduced pressure to completely remove the solvent component in advance for solid content conversion, followed by hydrolysis, and then extracting the succinic acid diester compound, other internal electron donor compounds added as needed, and the phthalic acid diester compound using an aromatic solvent.
[0108] As described above, the term "solid content conversion" in the present application document means that the content ratio of each component is calculated based on the solid content obtained by completely removing liquid components such as solvents.
[0109] The first solid olefin polymerization catalyst component constituting the solid olefin polymerization catalyst component mixture of the present invention preferably contains 2.0 to 5.0 mass % of titanium in terms of atomic weight, more preferably 2.5 to 4.5 mass % of titanium, and further preferably 3.5 to 4.5 mass % of titanium.
[0110] The first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention preferably contains 15.0 to 25.0 mass% of magnesium in terms of atomic weight, more preferably 16.0 to 23.0 mass% of magnesium, further preferably 17.0 to 22.0 mass% of magnesium, and further preferably 17.0 to 21.0 mass% of magnesium.
[0111] The first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention preferably contains 50.0 to 70.0% by mass of halogen in terms of atomic weight, more preferably 55.0 to 68.0% by mass of halogen, further preferably 58.0 to 67.0% by mass of halogen, and further preferably 60.0 to 66.0% by mass of halogen.
[0112] In the present application document, the content ratio of titanium atoms contained in the solid catalyst component for olefin polymerization refers to the value measured by the method described in JIS 8311-1997 "Quantitative method for titanium in titanium ore" (redox titration) using the solid catalyst component for olefin polymerization that has been previously dried under reduced pressure by heating to completely remove the solvent component.
[0113] In the present application, the content of magnesium atoms in the solid catalyst component for olefin polymerization refers to a value measured by the following EDTA titration method: the solid catalyst component for olefin polymerization, which has been previously dried by heating under reduced pressure to completely remove the solvent component, is dissolved in a hydrochloric acid solution and titrated with an EDTA solution.
[0114] In addition, in the present application document, the content ratio of halogen atoms contained in the solid catalyst component for olefin polymerization refers to the value measured by the following silver nitrate titration method: the solid catalyst component for olefin polymerization, which has been previously dried by heating under reduced pressure to completely remove the solvent component, is treated with a mixed solution of sulfuric acid and pure water to prepare an aqueous solution, and a prescribed amount is taken and the halogen is titrated with a standard silver nitrate solution.
[0115] The first solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization in the present invention may contain magnesium, titanium, halogen, and a succinic acid diester compound and, if necessary, other internal electron donating compounds, and may further contain polysiloxane.
[0116] When the first solid olefin polymerization catalyst component constituting the solid olefin polymerization catalyst component mixture of the present invention contains polysiloxane, stereoregularity and crystallinity of the obtained polymer can be easily improved during olefin polymerization, and fine powder of the generated polymer can be easily reduced.
[0117] Polysiloxane is a polymer with a siloxane bond (-Si-O- bond) in the main chain, also known as silicone oil, and has a viscosity of 0.02 to 100.00 cm at 25°C. 2 / s (2 to 10,000 centistokes), more preferably 0.03 to 5.00 cm 2 / s (3 to 500 centistokes) and is liquid or viscous at room temperature, chain, partially hydrogenated, cyclic or modified polysiloxane.
[0118] Examples of the chain polysiloxane include dimethyl polysiloxane and methylphenyl polysiloxane, examples of the partially hydrogenated polysiloxane include methyl hydrogen polysiloxane having a hydrogenation rate of 10 to 80%, and examples of the cyclic polysiloxane include at least one selected from hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, 2,4,6-trimethylcyclotrisiloxane and 2,4,6,8-tetramethylcyclotetrasiloxane.
[0119] The solid catalyst component mixture for olefin polymerization of the present invention contains the above-mentioned first solid catalyst component for olefin polymerization and a second solid catalyst component for olefin polymerization.
[0120] Examples of the second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention include a contact reaction product obtained by contacting and reacting raw material components serving as supply sources of magnesium, titanium and halogen with a phthalic acid diester compound serving as an internal electron donor compound in an organic solvent. Specifically, examples include a contact reaction product obtained by using a magnesium compound and a tetravalent titanium halide as raw material components serving as supply sources of magnesium, titanium and halogen, and contacting these raw materials with an internal electron donor compound containing a phthalic acid diester compound.
[0121] Specific examples of the magnesium compound and the tetravalent titanium halide include the same ones as those exemplified in the description of the first solid catalyst component for olefin polymerization.
[0122] In the second solid catalyst component for olefin polymerization constituting the solid catalyst mixture for olefin polymerization of the present invention, the phthalic acid diester compound is preferably a phthalic acid diester.
[0123] Examples of the phthalic acid diester include dimethyl phthalate, diethyl phthalate, di-n-propyl phthalate, diisopropyl phthalate, di-n-butyl phthalate, diisobutyl phthalate, methyl ethyl phthalate, (ethyl)-n-propyl phthalate, ethylisopropyl phthalate, (ethyl)-n-butyl phthalate, ethylisobutyl phthalate, and the like.
[0124] The second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention preferably contains 8.0 to 20.0% by mass, more preferably 9.0 to 17.5% by mass, and even more preferably 10.0 to 15.0% by mass of the phthalic acid diester compound in terms of solid content.
[0125] The second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention preferably contains 2.7 to 5.6 mol % of the phthalic acid diester compound in terms of solid content, more preferably 3.6 to 5.3 mol %, and even more preferably 4.5 to 5.0 mol %.
[0126] In the second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention, the ratio (D2 / T) of the content ratio of the phthalic acid diester compound (D2) to the content ratio of titanium (T) is preferably 0.025 to 0.072 in terms of mass ratio, more preferably 0.030 to 0.063, and further preferably 0.035 to 0.054.
[0127] In the second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention, the ratio (D2 / T) of the content ratio of the phthalic acid diester compound (D2) to the content ratio of titanium (T) is preferably 0.3 to 1.3 in terms of molar ratio, more preferably 0.5 to 1.2, and further preferably 0.7 to 1.1.
[0128] By setting the content of the phthalic acid diester compound in terms of solid content or the ratio (D2 / T) of the phthalic acid diester compound content (D2) to the titanium content (T) in the second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention within the above range, it is possible to easily produce olefin polymers having excellent melt fluidity and even better flexural modulus when used for olefin polymerization.
[0129] The second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention contains a phthalic acid diester compound as an internal electron donor compound as an essential component, but in addition to these internal electron donor compounds, it may also contain other internal electron donor compounds. As such other internal electron donor compounds, the same substances as those listed in the description of the above-mentioned first solid catalyst component for olefin polymerization can be listed.
[0130] In the second solid catalyst component for olefin polymerization constituting the solid catalyst component for olefin polymerization of the present invention, the content ratio of the succinic acid diester compound is suitably 0.2 mass % or less (0.0 to 0.2 mass %), more suitably 0.1 mass % or less (0.0 to 0.1 mass %), and further suitably 0.0 mass % (substantially containing no succinic acid diester (below the detection limit)).
[0131] The second solid olefin polymerization catalyst component constituting the solid olefin polymerization catalyst component mixture of the present invention preferably contains 2.0 to 5.0 mass% of titanium in terms of atomic weight, more preferably 2.5 to 4.5 mass% of titanium, and further preferably 3.5 to 4.5 mass% of titanium.
[0132] The second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention preferably contains 15.0 to 25.0 mass% of magnesium in terms of atomic weight, more preferably 16.0 to 23.0 mass% of magnesium, further preferably 17.0 to 22.0 mass% of magnesium, and further preferably 17.0 to 21.0 mass% of magnesium.
[0133] The second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention preferably contains 50.0 to 70.0% by mass of halogen in terms of atomic weight, more preferably 55.0 to 68.0% by mass of halogen, further preferably 58.0 to 67.0% by mass of halogen, and further preferably 60.0 to 66.0% by mass of halogen.
[0134] The method for measuring the content ratio of each constituent component of the second solid catalyst component for olefin polymerization is as described in the description of the first solid catalyst component for olefin polymerization.
[0135] The second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention may contain polysiloxane. Specific examples of the polysiloxane include those described in the description of the first solid catalyst component for olefin polymerization.
[0136] The solid catalyst component mixture for olefin polymerization of the present invention contains the first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization in a mass ratio of first solid catalyst component for olefin polymerization: second solid catalyst component for olefin polymerization = 37:63 to 87:13, preferably 37:63 to 86:14, more preferably 37:63 to 85:15.
[0137] It should be noted that the solid catalyst component mixture for olefin polymerization of the present invention refers to a mixture containing only the first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization.
[0138] The solid catalyst component mixture for olefin polymerization of the present invention contains the first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization in the above ratio, and can more efficiently produce an olefin polymer having excellent melt fluidity and flexural modulus when used for olefin polymerization.
[0139] In the solid catalyst component mixture for olefin polymerization of the present invention, a succinic acid diester compound is used as the internal electron donor compound constituting the first solid catalyst component for olefin polymerization, and a phthalic acid diester compound is used as the internal electron donor compound constituting the second solid catalyst component for olefin polymerization.
[0140] The content of the succinic diester compound in the solid catalyst component mixture for olefin polymerization of the present invention is preferably 4.7 to 14.9% by mass, more preferably 4.7 to 14.6% by mass, and even more preferably 4.7 to 14.3% by mass, in terms of solid content.
[0141] In the solid catalyst component mixture for olefin polymerization of the present invention, the content of the phthalic acid diester compound is preferably 2.2 to 7.9% by mass, more preferably 2.3 to 7.9% by mass, and even more preferably 2.5 to 7.9% by mass, in terms of solid content.
[0142] In the solid catalyst component mixture for olefin polymerization of the present invention, by setting the contents of the succinic diester compound and the phthalic diester compound within the above ranges, an olefin polymer having both high melt fluidity and rigidity can be easily produced when used for olefin polymerization.
[0143] Conventionally, it has been considered that succinic acid diester compounds are expensive in themselves when used as internal electron donating compounds in solid catalyst components for olefin polymerization, and that when used for olefin polymerization, it is difficult to improve the stereoregularity of the obtained olefin polymer. Therefore, succinic acid diester compounds have not been specifically used as internal electron donating compounds in solid catalyst components for olefin polymerization.
[0144] However, the present inventors have conducted intensive studies and found that a solid catalyst component for olefin polymerization containing a succinic acid diester compound as an internal electron donating compound can produce an olefin polymer having excellent flexural modulus (FM) when used for olefin polymerization.
[0145] On the other hand, according to the studies of the present inventors, it has been found that when a polypropylene having a flexural modulus (FM) of 1900 MPa or more is produced by using a solid catalyst component for olefin polymerization containing a succinic acid diester compound as an internal electron donating compound, the melt fluidity (melt flow rate (MFR)) of the obtained polypropylene is easily extremely reduced.
[0146] Under such circumstances, the present inventors have discovered that by using a substance containing a succinic acid diester compound as an internal electron donating compound as a first solid catalyst component for olefin polymerization, and using a substance containing a phthalic acid diester compound as an internal electron donating compound as a second solid catalyst component for olefin polymerization, and replacing the solid catalyst component of the conventional olefin polymerization catalyst with a mixture containing the first olefin polymerization solid catalyst component and the second olefin polymerization solid catalyst component in a prescribed ratio, it is possible to produce an olefin polymer having excellent melt fluidity and a higher flexural modulus than conventional olefin polymers when used for olefin polymerization, and the present invention has been completed based on this finding.
[0147] It is believed that when a mixture of solid catalyst components for olefin polymerization containing a plurality of internal electron donating compounds is used for olefin polymerization, a plurality of olefin polymers are produced by each solid catalyst component for olefin polymerization. However, olefin polymers having greatly different physical properties generally tend to be difficult to mix with each other, and therefore it is generally difficult to put it into practical use.
[0148] On the other hand, it is believed that for the solid catalyst component mixture for olefin polymerization of the present invention, by providing a mixture containing the first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization in a predetermined ratio to the polymerization of olefins, the first solid catalyst component for olefin polymerization generates a first olefin polymer having excellent bending modulus and a wide molecular weight distribution, and the first olefin polymer having a wide molecular weight distribution shows high compatibility with the second olefin polymer generated by the second solid catalyst component for olefin polymerization. It is also believed that the obtained olefin polymer (mixture of the first olefin polymer and the second olefin polymer) can exert excellent melt fluidity without significantly reducing the high bending modulus exerted exclusively by the first olefin polymer.
[0149] Thus, in the present invention, by using a specific solid catalyst component mixture for olefin polymerization instead of the solid catalyst component for olefin polymerization used in the past, an olefin polymer having high melt fluidity and rigidity can be easily produced without requiring a large amount of energy cost and without increasing the number of steps.
[0150] The solid catalyst component mixture for olefin polymerization of the present invention can be prepared by pre-mixing the first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization and providing the mixture to olefin polymerization in the form of a mixture, or the first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization can be separately loaded into the olefin polymerization system to prepare the mixture in the polymerization system.
[0151] The first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention can be produced by conventionally known methods.
[0152] The first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention are different in that each of them contains a succinic acid diester compound as an essential constituent as an internal electron donating compound, or contains a phthalic acid diester compound as an essential constituent as an internal electron donating compound, but are common in other aspects. Therefore, as the production method of the first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization, a method that is different in that each of them uses a succinic acid diester compound as an essential constituent as an internal electron donating compound, or uses a phthalic acid diester compound as an essential constituent as an internal electron donating compound, but is common in other aspects can also be used.
[0153] The first solid catalyst component for olefin polymerization or the second solid catalyst component for olefin polymerization constituting the solid catalyst component mixture for olefin polymerization of the present invention is preferably prepared by bringing the above-mentioned dialkoxymagnesium, titanium halide and internal electron donor compound (having either a succinic acid diester compound or a phthalic acid diester compound as an essential component) into contact with each other together with other components as required in the presence of an inert organic solvent.
[0154] In the present invention, the inert organic solvent is preferably an inert organic solvent that dissolves titanium halide and does not dissolve dialkoxymagnesium. Specifically, it includes at least one selected from saturated hydrocarbon compounds such as pentane, hexane, heptane, octane, nonane, decane, cyclohexane, methylcyclohexane, ethylcyclohexane, 1,2-diethylcyclohexane, methylcyclohexene, decalin, mineral oil, etc., aromatic hydrocarbon compounds such as benzene, toluene, xylene, ethylbenzene, etc., and halogenated hydrocarbon compounds such as o-dichlorobenzene, dichloromethane, 1,2-dichlorobenzene, carbon tetrachloride, and ethylene dichloride.
[0155] As the above-mentioned inactive organic solvent, it is preferred to use a saturated hydrocarbon compound or aromatic hydrocarbon compound that is liquid at room temperature and has a boiling point of about 50 to 200°C, among which it is preferably selected from one or more of hexane, heptane, octane, ethylcyclohexane, mineral oil, toluene, xylene, and ethylbenzene, and it is particularly preferred to select from any one or more of hexane, heptane, ethylcyclohexane and toluene.
[0156] As a method for producing the solid catalyst component for olefin polymerization constituting the olefin polymerization catalyst of the present invention, there can be mentioned a method in which, when preparing the first solid catalyst component for olefin polymerization or the second solid catalyst component for olefin polymerization by contacting dialkoxymagnesium, a titanium halide and an internal electron donating compound (comprising either a succinic acid diester compound or a phthalic acid diester compound as an essential component), the titanium halide is contacted with the dialkoxymagnesium multiple times, and when the titanium halide is contacted with the dialkoxymagnesium initially, 1.5 to 10.0 mol of the titanium halide is used relative to 1 mol of the dialkoxymagnesium, and the total amount of the titanium compound used is 5.0 to 18.0 mol relative to 1 mol of the dialkoxymagnesium, and further, the succinic acid diester compound or the phthalic acid diester compound is used in an amount of 0.10 to 0.20 mol relative to 1 mol of the dialkoxymagnesium, to obtain the target solid catalyst component for olefin polymerization (hereinafter referred to as method a for producing the solid catalyst component).
[0157] In the method a for preparing the solid catalyst component, the titanium halide and dialkoxymagnesium are brought into contact multiple times. When the titanium halide and dialkoxymagnesium are brought into contact for the first time, it is preferred to use 1.5 to 10.0 mol of the titanium halide per 1 mol of the dialkoxymagnesium, and to use 2.0 to 8.0 mol of the titanium halide per 1 mol of the dialkoxymagnesium. It is more preferred to use 2.0 to 5.0 mol of the titanium halide per 1 mol of the dialkoxymagnesium.
[0158] In the method a for preparing a solid catalyst component, by controlling the amount of the titanium halide to the dialkoxymagnesium to be used within the above range, a solid catalyst component for olefin polymerization having high activity can be prepared with a small amount of titanium halide.
[0159] In the method a for preparing the solid catalyst component, the total amount of the titanium compound used is 5.0 to 18.0 mol, preferably 5.0 to 15.0 mol, and more preferably 5.0 to 10.0 mol, per mol of dialkoxymagnesium.
[0160] In the method a for preparing the solid catalyst component, by controlling the total amount of the titanium compound used per 1 mol of the dialkoxymagnesium within the above range, a support capable of ensuring sufficiently high activity and optimally supporting the titanium halide and the succinic diester compound can be prepared.
[0161] In the method a for preparing the solid catalyst component, 0.10 to 0.20 mol of the succinic acid diester compound or the phthalic acid diester compound is used per 1 mol of the dialkoxymagnesium, preferably 0.10 to 0.18 mol of the succinic acid diester compound or the phthalic acid diester compound is used per 1 mol of the dialkoxymagnesium, and more preferably 0.10 to 0.15 mol of the succinic acid diester compound or the phthalic acid diester compound is used per 1 mol of the dialkoxymagnesium.
[0162] In the method a for preparing the solid catalyst component, by controlling the amount of the succinic acid diester compound or the phthalic acid diester compound used relative to 1 mol of the dialkoxymagnesium within the above range, excessive loading of the titanium halide on the carrier can be suppressed and the succinic acid diester compound or the phthalic acid diester compound can be fully loaded.
[0163] As a method a for preparing a solid catalyst component, more specifically, there can be cited, for example, a method as follows: dialkoxymagnesium and a titanium halide are suspended with a succinic acid diester compound or a phthalic acid diester compound in an inert hydrocarbon solvent, and after contacting them with heating for a predetermined time, a titanium halide is further added to the obtained suspension, and the mixture is contacted with heating to obtain a solid product, and the solid product is washed with a hydrocarbon solvent, thereby obtaining the target solid catalyst component for olefin polymerization.
[0164] The heating temperature is preferably 70 to 150°C, more preferably 80 to 120°C, and even more preferably 90 to 110°C.
[0165] The heating time is preferably 30 to 240 minutes, more preferably 60 to 180 minutes, and even more preferably 60 to 120 minutes.
[0166] The number of times the titanium halide is added to the above suspension is not particularly limited.
[0167] When the titanium halide is added to the suspension multiple times, each heating temperature may be within the above range, and the heating time during each addition may be within the above range.
[0168] It should be noted that in the above preparation method, other internal electron donating compounds may be further added while adding a succinic acid diester compound or a phthalic acid diester compound as an internal electron donating compound. Furthermore, the above contact may be carried out in the presence of other reaction reagents such as silicon, phosphorus, aluminum, and a surfactant.
[0169] According to the present invention, it is possible to provide a solid catalyst component mixture for olefin polymerization, which can easily produce an olefin polymer having both high melt fluidity and rigidity.
[0170] Next, the olefin polymerization catalyst of the present invention is described.
[0171] The olefin polymerization catalyst of the present invention is characterized in that it contains:
[0172] (I) A mixture of solid catalyst components for olefin polymerization of the present invention and
[0173] (II) One or more organoaluminum compounds selected from the compounds represented by the following general formula (1).
[0174] R 1 p AlQ 3-p (1)
[0175] (In the formula, R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is 0 < p ≤ 3.)
[0176] In the olefin polymerization catalyst of the present invention, the details of (I) the mixture of solid catalyst components for olefin polymerization of the present invention are as described above.
[0177] The olefin polymerization catalyst of the present invention contains (II) one or more selected from the compounds represented by the following general formula (1) as an organoaluminum compound.
[0178] R 1 p AlQ 3-p (1)
[0179] (In the formula, R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen, p is 0 < p ≤ 3, and when there are multiple Rs 1 , each R 1 is optionally the same or different from each other, and when there are multiple Qs, each Q is optionally the same or different from each other.)
[0180] In the compound represented by the above general formula (1), p is 0 < p ≤ 3. Specifically, examples of p include 1, 2, or 3.
[0181] Specific examples of the organoaluminum compound represented by the above general formula (1) include one or more selected from trialkylaluminums such as triethylaluminum, triisopropylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, triisobutylaluminum, haloalkylaluminums such as diethylaluminum chloride, diethylaluminum bromide, and diethylaluminum hydride. Preferably, one or more selected from haloalkylaluminums such as diethylaluminum chloride, trialkylaluminums such as triethylaluminum, tri-n-butylaluminum, and triisobutylaluminum are used. More preferably, one or more selected from triethylaluminum and triisobutylaluminum are used.
[0182] The olefin polymerization catalyst of the present invention preferably contains (III) an external electron donor compound.
[0183] In the olefin polymerization catalyst of the present invention, examples of the external electron donating compound (III) include silicon compounds represented by the following general formula (4).
[0184] R 7 r Si(NR 8 R 9 ) s (OR 10 ) 4-(r+s) (4)
[0185] (where r is 0 or 1 to 2, s is 0 or 1 to 2, r+s is 0 or 1 to 4, R 7 , R 8 or R 9 R is any group selected from a hydrogen atom, a linear or branched alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted cycloalkyl group, a phenyl group, an allyl group, and an aralkyl group, and may contain a heteroatom and may be the same or different from each other. 8 With R 9 They can also be bonded to form a ring shape, R 7 , R 8 and R 9 can be the same or different. 10 It is any group selected from an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group, a phenyl group, a vinyl group, an allyl group, and an aralkyl group, and may contain a heteroatom.
[0186] In the silicon compound represented by the above general formula (4), R 7 It is any group selected from the group consisting of a hydrogen atom, a linear or branched alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted cycloalkyl group, a phenyl group, an allyl group, and an aralkyl group, and may contain a hetero atom.
[0187] As R 7 , preferably a linear or branched alkyl group having 1 to 10 carbon atoms or a cycloalkyl group having 5 to 8 carbon atoms, and particularly preferably a linear or branched alkyl group having 1 to 8 carbon atoms or a cycloalkyl group having 5 to 8 carbon atoms.
[0188] In the silicon compound represented by the above general formula (4), R 8 or R 9 It is any group selected from the group consisting of a hydrogen atom, a linear or branched alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted cycloalkyl group, a phenyl group, an allyl group, and an aralkyl group, and may contain a hetero atom.
[0189] As R 8 or R 9 , preferably a linear or branched alkyl group having 1 to 10 carbon atoms, or a cycloalkyl group having 5 to 8 carbon atoms, and particularly preferably a linear or branched alkyl group having 1 to 8 carbon atoms, or a cycloalkyl group having 5 to 8 carbon atoms.
[0190] In addition, R 8 With R 9 can be bonded to form a ring shape. In this case, the ring-shaped (NR 8 R 9 ) is preferably perhydroquinolyl or perhydroisoquinolyl.
[0191] In the silicon compound represented by the above general formula (4), R 7 , R 8 and R 9 Can be the same or different.
[0192] In the silicon compound represented by the above general formula (4), R 10 It is any group selected from an alkyl group, a cycloalkyl group, a phenyl group, an allyl group and an aralkyl group having 1 to 4 carbon atoms, and may contain a hetero atom.
[0193] As R 10 , preferably a linear or branched alkyl group having 1 to 4 carbon atoms.
[0194] In the silicon compound represented by the general formula (4), r is 0 or 1 to 2. Specifically, r includes 0, 1 or 2.
[0195] In the silicon compound represented by the general formula (4), s is 0 or 1 to 2. Specifically, 0, 1 or 2 can be mentioned as s.
[0196] In the silicon compound represented by the general formula (4), r+s is 0 or 1 to 4. Specifically, r+s includes 0, 1, 2, 3 or 4.
[0197] As such silicon compounds represented by the above-mentioned general formula (4), specifically, there can be listed one or more organic silicon compounds selected from phenylalkoxysilane, alkylalkoxysilane, phenylalkylalkoxysilane, cycloalkylalkoxysilane, cycloalkylalkylalkoxysilane, (alkylamino)alkoxysilane, alkyl(alkylamino)alkoxysilane, alkyl(alkylamino)silane, alkylaminosilane and the like.
[0198] The silicon compound in which s is 0 in the general formula (4) is particularly preferably selected from di-n-propyldimethoxysilane, diisopropyldimethoxysilane, di-n-butyldimethoxysilane, diisobutyldimethoxysilane, di-tert-butyldimethoxysilane, tert-butylmethyldimethoxysilane, tert-butylethyldimethoxysilane, di-n-butyldiethoxysilane, tert-butyltrimethoxysilane, tert-butyltriethoxysilane, dicyclohexyldimethoxysilane, dicyclohexyldiethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexylmethyldiethoxysilane, The organic silicon compound may be one or more of the following: dimethoxysilane, cyclohexylethyldimethoxysilane, cyclohexylethyldiethoxysilane, dicyclopentyldimethoxysilane, dicyclopentyldiethoxysilane, cyclopentylmethyldimethoxysilane, cyclopentylmethyldiethoxysilane, cyclopentylethyldiethoxysilane, cyclohexylcyclopentyldimethoxysilane, cyclohexylcyclopentyldiethoxysilane, 3-methylcyclohexylcyclopentyldimethoxysilane, 4-methylcyclohexylcyclopentyldimethoxysilane, and 3,5-dimethylcyclohexylcyclopentyldimethoxysilane.
[0199] Examples of the silicon compound in which s in the general formula (4) is 1 or 2 include one or more organic silicon compounds selected from di(alkylamino)dialkoxysilane, (alkylamino)(cycloalkylamino)dialkoxysilane, (alkylamino)(alkyl)dialkoxysilane, di(cycloalkylamino)dialkoxysilane, vinyl(alkylamino)dialkoxysilane, allyl(alkylamino)dialkoxysilane, (alkoxyamino)trialkoxysilane, (alkylamino)trialkoxysilane, (cycloalkylamino)trialkoxysilane, and the like. Particularly preferred are ethyl( tert-butylamino)dimethoxysilane, cyclohexyl(cyclohexylamino)dimethoxysilane, ethyl(tert-butylamino)dimethoxysilane, bis(cyclohexylamino)dimethoxysilane, bis(perhydroisoquinolyl)dimethoxysilane, bis(perhydroquinolyl)dimethoxysilane, ethyl(isoquinolyl)dimethoxysilane, diethylaminotrimethoxysilane, diethylaminotriethoxysilane, etc., wherein the organic silicon compound is one or more selected from bis(perhydroisoquinolyl)dimethoxysilane, diethylaminotrimethoxysilane, or diethylaminotriethoxysilane.
[0200] It should be noted that the silicon compound represented by the general formula (4) may be used in combination of two or more.
[0201] The olefin polymerization catalyst of the present invention comprises (I) the solid catalyst component for olefin polymerization of the present invention, (II) the organoaluminum compound represented by the general formula (2), and (III) an external electron donating compound as required, that is, a contact product thereof.
[0202] The catalyst for olefin polymerization of the present invention can be prepared by bringing (I) the solid catalyst component for olefin polymerization of the present invention, (II) the organoaluminum compound represented by the general formula (2), and (III) the external electron-donating compound as required into contact in the absence of olefins, or in the presence of olefins (in a polymerization system) as described below.
[0203] In the olefin polymerization catalyst of the present invention, the content ratio of each component is arbitrary as long as it does not affect the effect of the present invention, and is not particularly limited. Generally, it is preferred that 1 to 2000 mol of the above-mentioned (II) organoaluminum compound is contained, and more preferably 50 to 1000 mol of the above-mentioned (II) organoaluminum compound is contained, relative to 1 mol of titanium atoms in the above-mentioned (I) solid catalyst component mixture for olefin polymerization. In addition, the olefin polymerization catalyst of the present invention preferably contains 0.002 to 10.000 mol of the above-mentioned (III) external electron donating compound, and more preferably 0.010 to 2.000 mol of the above-mentioned (III) external electron donating compound, and further preferably 0.010 to 0.500 mol of the above-mentioned (III) external electron donating compound, relative to 1 mol of the above-mentioned (II) organoaluminum compound.
[0204] According to the present invention, it is possible to provide an olefin polymerization catalyst capable of easily producing an olefin polymer having both high melt fluidity and rigidity.
[0205] Next, the method for producing the olefin polymer of the present invention will be described.
[0206] The method for producing an olefin polymer of the present invention is characterized by polymerizing olefins using the olefin polymerization catalyst of the present invention.
[0207] In the method for producing an olefin polymer of the present invention, the polymerization of olefins may be either homopolymerization or copolymerization.
[0208] In the method for producing olefin polymers of the present invention, olefins to be polymerized include one or more selected from ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, vinylcyclohexane, etc., among which one or more selected from ethylene, propylene and 1-butene are preferred, and propylene is more preferred.
[0209] When the olefin is propylene, propylene may be homopolymerized or copolymerized with other α-olefins.
[0210] Examples of the olefins to be copolymerized with propylene include one or more selected from ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, vinylcyclohexane and the like.
[0211] When the olefin polymerization catalyst of the present invention is prepared in the presence of olefins (in a polymerization system), the amount ratio of each component is arbitrary as long as it does not affect the effect of the present invention, and is not particularly limited. Generally, it is preferred that 1 to 2000 mol, more preferably 50 to 1000 mol, of the above-mentioned organoaluminum compound is contacted with 1 mol of titanium atoms in the above-mentioned solid catalyst component mixture for olefin polymerization. In addition, it is preferred that 0.002 to 10.000 mol, more preferably 0.01 to 2 mol, and even more preferably 0.010 to 0.500 mol of the external electron donating compound selected from the silicon compound represented by the above-mentioned general formula (4) is contacted with 1 mol of the above-mentioned organoaluminum compound.
[0212] The order of contacting the components constituting the above-mentioned olefin polymerization catalyst is arbitrary. It is preferred that the above-mentioned organic aluminum compound is first charged into the polymerization system, and then an external electron-donating compound is charged and contacted as needed, and then the above-mentioned solid catalyst component mixture for olefin polymerization is charged and contacted.
[0213] The above-mentioned solid catalyst component mixture for olefin polymerization can be prepared by mixing the first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization and charging the mixture into the polymerization system, or the first solid catalyst component for olefin polymerization and the second solid catalyst component for olefin polymerization can be separately charged and prepared as a mixture in the polymerization system.
[0214] The method for producing an olefin polymer of the present invention may be carried out in the presence or absence of an organic solvent.
[0215] In addition, olefin monomers such as propylene can be used in either a gas or liquid state. The polymerization temperature is preferably 200°C or less, more preferably 100°C or less, and the polymerization pressure is preferably 10 MPa or less, more preferably 5 MPa or less. In addition, the polymerization of olefins can be any of a continuous polymerization method and a batch polymerization method. Furthermore, the polymerization reaction can be carried out in one stage or in two or more stages.
[0216] Furthermore, when olefins are polymerized using the olefin polymerization catalyst of the present invention (also referred to as main polymerization), in order to further improve the catalytic activity, stereoregularity and particle properties of the generated polymer, it is preferred to carry out prepolymerization before the main polymerization. During the prepolymerization, the same olefins or monomers such as styrene as those used in the main polymerization can be used.
[0217] When conducting prepolymerization, the order of contacting the components constituting the above-mentioned olefin polymerization catalyst and the monomer (olefin) is arbitrary. It is preferred that in a prepolymerization system set to an inert gas atmosphere or an olefin gas atmosphere, the organic aluminum compound is first charged, and then the above-mentioned olefin polymerization solid catalyst component is charged and brought into contact, and then olefins such as propylene are brought into contact alone, or a mixture of olefins such as propylene and one or more other olefins are brought into contact.
[0218] In the above-mentioned prepolymerization, when an external electron donating compound is further charged into the prepolymerization system, it is preferred that, in the prepolymerization system set to an inert gas atmosphere or an olefin gas atmosphere, the organic aluminum compound is first charged, and then the external electron donating compound is charged and brought into contact, and then, after the above-mentioned solid catalyst component mixture for olefin polymerization is brought into contact, olefins such as propylene are brought into contact alone, or a mixture of olefins such as propylene and one or more other olefins are brought into contact.
[0219] In the method for producing olefin polymers of the present invention, examples of polymerization methods include slurry polymerization using a solvent of an inert hydrocarbon compound such as cyclohexane or heptane, bulk polymerization using a solvent such as liquefied propylene, and gas phase polymerization using substantially no solvent, with bulk polymerization or gas phase polymerization being preferred.
[0220] When copolymerizing propylene with other α-olefin monomers, typical examples include random copolymerization in which propylene and a small amount of ethylene are used as comonomers and polymerization is carried out in one stage; and so-called propylene-ethylene block copolymerization in which propylene is homopolymerized in the first stage (first polymerization tank) and propylene and other α-olefins such as ethylene are copolymerized in the second stage (second polymerization tank) or more stages (multi-stage polymerization tanks), preferably block copolymerization of propylene and other α-olefins.
[0221] The block copolymer obtained by block copolymerization is a polymer containing segments in which the monomer composition of two or more kinds of monomers changes continuously, and refers to a copolymer in which polymer chains (segments) with different primary structures of the polymer such as monomer type, comonomer type, comonomer composition, comonomer content, comonomer arrangement, stereoregularity, etc. are connected in one molecular chain in two or more forms.
[0222] In the method for producing olefin polymers of the present invention, the block copolymerization reaction of propylene and other α-olefins can be generally carried out by contacting propylene alone or with a small amount of α-olefin (ethylene etc.) in the presence of the olefin polymerization catalyst of the present invention in the first stage, and then contacting propylene with an α-olefin (ethylene etc.) in the second stage.
[0223] It should be noted that the polymerization reaction of the first stage may be repeated multiple times, and the polymerization reaction of the second stage may be repeated multiple times to be carried out in a multi-stage reaction.
[0224] Regarding the block copolymerization reaction of propylene and other α-olefins, it is preferred to specifically carry out the polymerization by adjusting the polymerization temperature and time in the first stage so that the proportion of the polypropylene part (occupying in the finally obtained copolymer) becomes 20 to 90 mass %, and then introduce propylene and ethylene or other α-olefins in the second stage to carry out the polymerization in such a way that the proportion of the rubber part such as ethylene-propylene rubber (EPR) (occupying in the finally obtained copolymer) becomes 10 to 80 mass %.
[0225] The polymerization temperature in both the first stage and the second stage is preferably 200° C. or less, more preferably 100° C. or less, further preferably 65 to 80° C., and the polymerization pressure is preferably 10 MPa or less, more preferably 6 MPa or less, further preferably 5 MPa or less.
[0226] In the above copolymerization reaction, either a continuous polymerization method or a batch polymerization method may be adopted, and the polymerization reaction may be carried out in one stage or in two or more stages.
[0227] The polymerization time (residence time in the reactor) is preferably 1 minute to 5 hours in each polymerization stage of the first or second polymerization stage, or in the case of continuous polymerization.
[0228] Examples of the polymerization method include slurry polymerization using a solvent such as cyclohexane or heptane, bulk polymerization using a solvent such as liquefied propylene, and gas phase polymerization using substantially no solvent. Preferred are bulk polymerization and gas phase polymerization.
[0229] In particular, ethylene-propylene block copolymers contain an EPR component (copolymer component of ethylene and propylene). If the EPR component seeps out onto the particle surface of the polymer, the particles become sticky (adhesive) and the fluidity deteriorates. In polymer manufacturing equipment, the deterioration of particle fluidity becomes a major cause of reduced plant equipment operability, so it is desirable to select a polymer manufacturing method that can inhibit the EPR component from seeping out onto the particle surface.
[0230] In the olefin polymer obtained by the production method of the present invention, the melt flow rate (MFR) representing the melt fluidity of the olefin polymer can be within a high value range capable of maintaining the excellent moldability of the olefin polymer, and can be 80 to 120 g / 10 minutes, preferably 100 to 120 g / 10 minutes.
[0231] In addition, in this application document, the melt flow rate (MFR) refers to the value measured based on ASTM D1238 and JIS K7210.
[0232] When the melt flow rate (MFR) of the olefin polymer obtained by the production method of the present invention is within a specific range (80 to 120 g / 10 min), the flexural modulus (FM) is 1900 MPa or more, preferably 1900 to 2500 MPa, and more preferably 2000 to 2400 MPa.
[0233] In the olefin polymer obtained by the production method of the present invention, by setting the flexural modulus (FM) within the above range, excellent rigidity can be easily exhibited.
[0234] Generally, it is known that in an olefin polymer obtained using an olefin polymerization catalyst (comprising a solid catalyst component for olefin polymerization), melt fluidity (melt flow rate (MFR)) and flexural modulus (FM) are in a trade-off relationship.
[0235] In general, even when a polypropylene having a flexural modulus (FM) of 1900 MPa or more is produced using a solid catalyst component for olefin polymerization containing a succinic diester compound as an internal electron donating compound, the melt flow rate (MFR) of the obtained polypropylene tends to be extremely low.
[0236] However, in the olefin polymer obtained by the production method of the present invention, even if the melt flow rate (MFR) is in the specific high value range of 80 to 120 g / 10 min, an olefin polymer having a flexural modulus (FM) of 1900 MPa or more can be obtained.
[0237] It should be noted that in the present application document, the flexural modulus (FM) of the above copolymer refers to: using NEX30III3EG manufactured by Nissei Plastic Industry Co., Ltd., injection molding a multi-purpose test piece type A1 specified in JIS K7139 under the conditions of a molding temperature of 200°C and a mold temperature of 40°C, cutting a test piece with a thickness of 4.0 mm, a width of 10.0 mm, and a length of 80.0 mm from the center of the test piece, and conditioning the cut test piece in a constant temperature chamber adjusted to 23°C for 72 hours, and then measuring the value (unit: MPa) based on JIS K7171 at a measurement atmosphere temperature of 23°C.
[0238] The olefin polymer obtained by the production method of the present invention can easily exhibit excellent rigidity by satisfying the above-mentioned requirements for the flexural modulus.
[0239] In order to maintain the excellent rigidity of the olefin polymer, the proportion (F) of the oriented layer in the cross section of the injection molded article formed of the olefin polymer obtained by the production method of the present invention is preferably 16.0 to 28.0%, more preferably 18.0 to 28.0%.
[0240] Here, in the present application document, the orientation layer in the cross section of the injection molded body formed by the olefin polymer refers to the layer on the surface with high birefringence (also called the epidermis layer). The cross section of the injection molded body is formed with the above-mentioned orientation layer and the internal non-oriented layer (also called the core layer), which are visually recognized as clearly separated layers. Since the orientation layer is highly oriented, it is expected that the elastic modulus and strength are large. As a result, it is believed that the thicker the orientation layer, the greater the overall elastic modulus and strength of the molded body. On the other hand, the elastic modulus and strength of the injection molded body with too thin an orientation layer are insufficient, and the injection molded body with too thick an orientation layer will destroy the balance between the orientation layer and the non-oriented layer, and it is easy to break in either case. In the olefin polymer obtained by the manufacturing method of the present invention, by making the ratio (F) of the above-mentioned orientation layer within the above-mentioned range, it is possible to maintain a high bending modulus and easily exert excellent rigidity.
[0241] In addition, in this application document, the ratio (F) of the oriented layer in the cross section of the injection molded product formed of the above-mentioned olefin-based polymer refers to a value measured by the method shown below.
[0242] 1. Formation of molded products
[0243] According to JIS K 7152-1 and JIS K 6921-2, an olefin polymer was injection molded under the following conditions to obtain a Figure 1 The injection molded body shown has a dumbbell-shaped appearance.
[0244] [Injection molding conditions]
[0245] Device: NEX-III-3EG manufactured by Nissei Plastic Industry Co., Ltd.
[0246] Test piece type: Multi-purpose test piece type A1 as specified in JIS K 7139
[0247] Resin melting temperature: 200°C
[0248] Mold temperature: 40℃
[0249] Injection speed: 180 mm / s
[0250] Holding pressure: 50MPa-40 seconds
[0251] 2. Preparation of measurement samples (thin slices for polarizing microscope observation)
[0252] (1) Figure 1 As shown, the molded product is cut at a position c1 about 7 cm long in the resin running direction MD from the gate G of the obtained molded product, and then cut at a position c2 about 2 cm long in the resin running direction MD from the position c1, and then cut at a direction perpendicular to the resin running direction MD to obtain Figure 2 The cut product S1 shown in (a).
[0253] (2) Figure 2 As shown in (a), the central portion (position c3) of the cut product S1 obtained in (1) is cut parallel to the resin running direction MD to obtain Figure 2 The cut product S2 shown in (b).
[0254] (3) Figure 2 As shown in (b), a rotary slicer device (RX-860 manufactured by Yamato Koki Kogyo Co., Ltd.) was used to cut a cut product S2 at position c4 in parallel with the resin travel direction MD and with a thickness of 30 μm to obtain Figure 2 The thin sheet-shaped measurement sample S3 shown in (c) .
[0255] (4) Figure 2 (d) is a schematic diagram showing the obtained thin sheet-like measurement sample S3, Figure 2 The left side of (d) shows Figure 2 (c) is a side view of the corresponding thin sheet-like measurement sample S3, Figure 2 The figure on the right side of (d) is a front view of a thin sheet-like measurement sample S3.
[0256] 3. Polarized light microscope observation
[0257] Figure 3 yes Figure 2 (d) is an enlarged view of the front view of the thin sheet-like measurement sample S3 shown in the right figure.
[0258] The above-mentioned measurement sample S3 was observed using a polarizing microscope (EPCLIPSE LV-100NDA manufactured by NIKON CORPORATION), and the core layer c and the orientation layers h1 and h2 were determined. The thickness of the core layer was set to Tc, and the thickness of the orientation layer was set to Th1 and Th2. The ratio F (%) of the thickness of the orientation layer relative to the thickness of the molding layer was calculated by the following formula (β).
[0259] F(%)={(Th1+Th2) / (Th1+Tc+Th2)}×100(β)
[0260] The thickness Tc of the core layer and the thicknesses Th1 and Th2 of the orientation layers are the arithmetic mean values of the thickness of the core layer c and the thicknesses of the orientation layers h1 and h2 measured at three arbitrary locations of the measurement sample S3.
[0261] According to the present invention, it is possible to provide a method for producing an olefin-based polymer having high melt fluidity and excellent moldability, and having a further high flexural modulus and excellent rigidity.
[0262] Example
[0263] Next, the present invention will be described in more detail with reference to Examples, but these are merely illustrative and do not limit the present invention.
[0264] (Performance Evaluation)
[0265] In Examples and Comparative Examples, each performance evaluation was performed by the following methods.
[0266] <Titanium Atom Content Ratio>
[0267] The content of titanium atoms is measured according to the method of JIS 8311-1997 using a solid catalyst component for olefin polymerization from which the solvent component has been completely removed by heating and drying under reduced pressure.
[0268] <Content ratio of internal electron donating compound>
[0269] The content ratio of the internal electron donating compound (succinic acid diester compound and phthalic acid diester compound) was determined as follows: after hydrolyzing the solid catalyst component for olefin polymerization from which the solvent component was completely removed by heating and drying under reduced pressure, the internal electron donating compound was extracted using an aromatic solvent, and the solution was measured using a gas chromatograph (GC-14B manufactured by Shimadzu Corporation) under the following conditions (gas chromatography FID method), thereby determining the content ratio of the internal electron donating compound. In addition, the number of moles of each component was determined based on the measurement results of the gas chromatograph using a calibration curve measured in advance at a known concentration.
[0270] [Measurement conditions]
[0271] Column: Packed column (φ2.6×2.1 m, Silicone SE-30 10%, Chromosorb WAW DMCS 80 / 100, manufactured by GL Sciences Inc.)
[0272] Detector: FID (Flame Ionization Detector)
[0273] Carrier gas: Helium, flow rate 40mL / min
[0274] Measurement temperature: Vaporization chamber 280°C, column 225°C, detector 280°C
[0275] <Polymerization Activity>
[0276] The polymerization activity per 1 g of the mixed solid catalyst component was determined by the following formula (α).
[0277] Polymerization activity (g / g-cat) = mass of polymer (g) / mass of mixed solid catalyst component (g) (α)
[0278] <Melt fluidity (MFR)>
[0279] The melt flow rate (MFR) (g / 10 minutes) indicating the melt fluidity of a polymer was measured in accordance with ASTM D 1238 and JIS K 7210.
[0280] <Flexural modulus (FM)>
[0281] The flexural modulus (FM) of the polymer was measured at a measurement atmosphere temperature of 23°C in accordance with JIS K7171 using an injection molded test piece (thickness 4.0 mm, width 10.0 mm, length 80 mm) produced using NEX30III3EG manufactured by Nissei Plastic Industry Co., Ltd. at a molding temperature of 200°C and a mold temperature of 40°C.
[0282] <Ratio of Oriented Layer in Cross Section of Injection Molded Plate Formed by Polymer (F)>
[0283] 1. Formation of molded products
[0284] According to JIS K 7152-1 and JIS K 6921-2, an olefin polymer was injection molded under the following conditions to obtain a Figure 1 The injection molded body shown has a dumbbell-shaped appearance.
[0285] [Injection molding conditions]
[0286] Device: NEX-III-3EG manufactured by Nissei Plastic Industry Co., Ltd.
[0287] Test piece type: Multi-purpose test piece type A1 as specified in JIS K 7139
[0288] Resin melting temperature: 200°C
[0289] Mold temperature: 40℃
[0290] Injection speed: 180 mm / s
[0291] Holding pressure: 50MPa-40 seconds
[0292] 2. Preparation of measurement samples (thin slices for polarizing microscope observation)
[0293] (1) Figure 1 As shown, the molded product is cut at a position c1 about 7 cm long in the resin running direction MD from the gate G of the obtained molded product, and then cut at a position c2 about 2 cm long in the resin running direction MD from the position c1, and then cut at a direction perpendicular to the resin running direction MD to obtain Figure 2 The cut product S1 shown in (a).
[0294] (2) Figure 2 As shown in (a), the central portion (position c3) of the cut product S1 obtained in (1) is cut parallel to the resin running direction MD to obtain Figure 2 The cut product S2 shown in (b).
[0295] (3) Figure 2 As shown in (b), a rotary slicer device (RX-860 manufactured by Yamato Koki Kogyo Co., Ltd.) was used to cut a cut product S2 at position c4 in parallel with the resin travel direction MD and with a thickness of 30 μm to obtain Figure 2 The thin sheet-shaped measurement sample S3 shown in (c) .
[0296] (4) Figure 2 (d) is a schematic diagram showing the obtained thin sheet-like measurement sample S3, Figure 2 The left side of (d) shows Figure 2 (c) is a side view of the corresponding thin sheet-like measurement sample S3, Figure 2 The figure on the right side of (d) is a front view of a thin sheet-like measurement sample S3.
[0297] 3. Polarized light microscope observation
[0298] Figure 3 yes Figure 2 (d) is an enlarged view of the front view of the thin sheet-like measurement sample S3 shown in the right figure.
[0299] The above-mentioned measurement sample S3 was observed using a polarizing microscope (EPCLIPSE LV-100NDA manufactured by NIKON CORPORATION), and the core layer c and the orientation layers h1 and h2 were determined. The thickness of the core layer was set to Tc, and the thickness of the orientation layer was set to Th1 and Th2. The ratio F (%) of the thickness of the orientation layer relative to the thickness of the molding layer was calculated by the following formula (β).
[0300] F(%)={(Th1+Th2) / (Th1+Tc+Th2)}×100(β)
[0301] The thickness Tc of the core layer and the thicknesses Th1 and Th2 of the orientation layers are the arithmetic mean values of the thickness of the core layer c and the thicknesses of the orientation layers h1 and h2 measured at three arbitrary locations of the measurement sample S3.
[0302] (Production Example 1)
[0303] <Synthesis of Solid Component>
[0304] 25 mL of toluene and 20 mL of titanium tetrachloride were added to a 500 mL round-bottom flask equipped with a stirrer and replaced with nitrogen. 10 g of ethoxymagnesium and 30 mL of toluene were placed in a separately prepared 300 mL round-bottom flask to prepare a suspension.
[0305] Next, the suspension solution was added to a 500 mL round-bottom flask in several portions, aged, and then heated. When the temperature reached 60°C, 4.0 mL (3.9 g) of diethyl 2,2-diisopropylsuccinate was added, and the temperature was further raised to 110°C.
[0306] Then, the mixture was reacted for 3 hours while being stirred while maintaining the temperature at 110°C.
[0307] After the reaction was completed, washing with 80 mL of toluene at 100° C. was repeated 4 times, and then 15 mL of titanium tetrachloride and 45 mL of toluene were added again, the temperature was raised to 100° C., and the mixture was reacted while stirring for 15 minutes. Furthermore, 15 mL of titanium tetrachloride and 45 mL of toluene were added again, the temperature was raised to 100° C., and the mixture was reacted twice while stirring for 15 minutes. After the reaction was completed, washing with 75 mL of n-heptane at 60° C. was repeated 6 times, and then the mixture was dried under reduced pressure to obtain a powdery solid component (a1) (first solid catalyst component for olefin polymerization).
[0308] The obtained solid component (a1) had a titanium content of 3.4% by mass (0.071 mol%) and a diethyl 2,3-diisopropylsuccinate (succinic acid diester compound) content of 18.7% by mass (0.072 mol%).
[0309] (Production Example 2)
[0310] <Synthesis of Solid Component>
[0311] 40 mL of toluene and 20 mL of titanium tetrachloride were added to a 500 mL round-bottom flask equipped with a stirrer and the internal atmosphere was replaced with nitrogen. 10 g of ethoxymagnesium and 45 mL of toluene were placed in a separately prepared 300 mL round-bottom flask, and 2.6 mL of di-n-butyl phthalate (phthalic acid diester compound) was added to prepare a suspension state.
[0312] Next, the suspension solution was added to a 500 mL round-bottom flask in multiple portions, aged, and then heated. When the temperature reached 60°C, 1.2 mL (1.3 g) of di-n-butyl phthalate was added, and the temperature was further raised to 110°C.
[0313] Then, the mixture was reacted for 2 hours while being stirred while maintaining the liquid temperature at 110°C.
[0314] After the reaction was completed, the supernatant was removed, and washing with 100 mL of toluene was repeated 4 times, and then 20 mL of titanium tetrachloride and 80 mL of toluene were added again, and the liquid temperature was maintained at 105° C. for 2 hours.
[0315] After the reaction was completed, washing with 100 mL of n-heptane was repeated 8 times, and then the mixture was dried under reduced pressure to obtain a powdery solid component (b1) (a second solid catalyst component for olefin polymerization).
[0316] The obtained solid component (b1) had a titanium content of 1.9% by mass (0.040 mol%) and a di-n-butyl phthalate (phthalic acid diester compound) content of 10.5% by mass (0.040 mol%).
[0317] (Example 1)
[0318] <Preparation of mixed solid catalyst component>
[0319] A loading container purged with nitrogen was prepared, and 2.0 mg of the solid component (a1) obtained in Production Example 1 and 5.9 mg of the solid component (b1) obtained in Production Example 2 were charged to obtain a mixed solid catalyst component (A1) (solid catalyst component mixture for olefin polymerization).
[0320] Tables 1 and 2 show the content ratios of the respective components in the obtained mixed solid catalyst component (A1).
[0321] <Formation of Polymerization Catalyst and Polymerization Reaction>
[0322] Into a 2.0 liter autoclave equipped with a stirrer and purged with nitrogen were placed 1.32 mmol of triethylaluminum, 0.26 mmol of dicyclopentylbis(ethylamino)silane (T01) and 0.0038 mmol of the mixed solid catalyst component (A1) in terms of titanium atoms to prepare a polymerization catalyst.
[0323] Then, 1.5 liters of hydrogen and 1.4 liters of liquefied propylene were charged, and prepolymerization was carried out at 20°C for 5 minutes. The temperature was then raised and a polymerization reaction was carried out at 70°C for 1 hour.
[0324] The propylene polymerization activity (PP polymerization activity) per 1 g of the solid catalyst component, the melt flowability (MFR) of the polymer, the flexural modulus (FM) of the polymer, and the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer were measured. The results are shown in Table 3.
[0325] In addition, a polarizing microscope image of a thin sheet-like measurement sample S3 used for measuring the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer is shown in FIG. Figure 4 .
[0326] (Example 2)
[0327] <Preparation of mixed solid catalyst component>
[0328] A loading container purged with nitrogen was prepared, and 3.4 mg of the solid component (a1) obtained in Production Example 1 and 3.4 mg of the solid component (b1) obtained in Production Example 2 were charged to obtain a mixed solid catalyst component (A2) (solid catalyst component mixture for olefin polymerization).
[0329] Tables 1 and 2 show the content ratios of the respective components in the obtained mixed solid catalyst component (A2).
[0330] <Formation of Polymerization Catalyst and Polymerization Reaction>
[0331] Into a 2.0 liter autoclave equipped with a stirrer and purged with nitrogen were placed 1.32 mmol of triethylaluminum, 0.26 mmol of dicyclopentylbis(ethylamino)silane (T01) and 0.0038 mmol of the mixed solid catalyst component (A2) in terms of titanium atoms to prepare a polymerization catalyst.
[0332] Then, 1.5 liters of hydrogen and 1.4 liters of liquefied propylene were charged, and prepolymerization was carried out at 20°C for 5 minutes. The temperature was then raised and a polymerization reaction was carried out at 70°C for 1 hour.
[0333] The propylene polymerization activity (PP polymerization activity) per 1 g of the solid catalyst component, the melt flowability (MFR) of the polymer, the flexural modulus (FM) of the polymer, and the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer were measured. The results are shown in Table 3.
[0334] In addition, a polarizing microscope image of a thin sheet-like measurement sample S3 used for measuring the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer is shown in FIG. Figure 5 .
[0335] (Example 3)
[0336] <Preparation of mixed solid catalyst component>
[0337] A loading container purged with nitrogen was prepared, and 4.5 mg of the solid component (a1) obtained in Production Example 1 and 1.5 mg of the solid component (b1) obtained in Production Example 2 were charged to obtain a mixed solid catalyst component (A3) (solid catalyst component mixture for olefin polymerization).
[0338] Tables 1 and 2 show the content ratios of the respective components in the obtained mixed solid catalyst component (A3).
[0339] <Formation of Polymerization Catalyst and Polymerization Reaction>
[0340] Into a 2.0 liter autoclave equipped with a stirrer and purged with nitrogen were placed 1.32 mmol of triethylaluminum, 0.26 mmol of dicyclopentylbis(ethylamino)silane (T01) and 0.0038 mmol of the mixed solid catalyst component (A3) in terms of titanium atoms to prepare a polymerization catalyst.
[0341] Then, 1.5 liters of hydrogen and 1.4 liters of liquefied propylene were charged, and prepolymerization was carried out at 20°C for 5 minutes. The temperature was then raised and a polymerization reaction was carried out at 70°C for 1 hour.
[0342] The propylene polymerization activity (PP polymerization activity) per 1 g of the solid catalyst component, the melt flowability (MFR) of the polymer, the flexural modulus (FM) of the polymer, and the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer were measured. The results are shown in Table 3.
[0343] In addition, a polarizing microscope image of a thin sheet-like measurement sample S3 used for measuring the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer is shown in FIG. Figure 6 .
[0344] (Comparative Example 1)
[0345] In Comparative Example 1, the solid component (a1) (first solid catalyst component for olefin polymerization) obtained in Production Example 1 was used as the solid catalyst component (B1) in the formation of the polymerization catalyst and the polymerization reaction described later.
[0346] Tables 1 and 2 show the content ratios of the respective components in the solid catalyst component (B1).
[0347] <Formation of Polymerization Catalyst and Polymerization Reaction>
[0348] Into a 2.0 liter autoclave equipped with a stirrer and purged with nitrogen were placed 1.32 mmol of triethylaluminum, 0.26 mmol of dicyclopentylbis(ethylamino)silane (T01) and 0.0038 mmol of the mixed solid catalyst component (B1) in terms of titanium atoms to prepare a polymerization catalyst.
[0349] Then, 1.5 liters of hydrogen and 1.4 liters of liquefied propylene were charged, and prepolymerization was carried out at 20°C for 5 minutes. The temperature was then raised and a polymerization reaction was carried out at 70°C for 1 hour.
[0350] The propylene polymerization activity (PP polymerization activity) per 1 g of the solid catalyst component, the melt flowability (MFR) of the polymer, the flexural modulus (FM) of the polymer, and the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer were measured. The results are shown in Table 3.
[0351] In addition, a polarizing microscope image of a thin sheet-like measurement sample S3 used for measuring the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer is shown in FIG. Figure 7 .
[0352] (Comparative Example 2)
[0353] In Comparative Example 2, the solid component (b1) (second solid catalyst component for olefin polymerization) obtained in Production Example 2 was used as the solid catalyst component (B2) in the formation of the polymerization catalyst and the polymerization reaction described later.
[0354] Tables 1 and 2 show the content ratios of the respective components in the solid catalyst component (B2).
[0355] <Formation of Polymerization Catalyst and Polymerization Reaction>
[0356] Into a 2.0 liter autoclave equipped with a stirrer and purged with nitrogen were placed 1.32 mmol of triethylaluminum, 0.26 mmol of dicyclopentylbis(ethylamino)silane (T01) and 0.0024 mmol of the mixed solid catalyst component (B2) in terms of titanium atoms to prepare a polymerization catalyst.
[0357] Then, 1.5 liters of hydrogen and 1.4 liters of liquefied propylene were charged, and prepolymerization was carried out at 20°C for 5 minutes. The temperature was then raised and a polymerization reaction was carried out at 70°C for 1 hour.
[0358] The propylene polymerization activity (PP polymerization activity) per 1 g of the solid catalyst component, the melt flowability (MFR) of the polymer, the flexural modulus (FM) of the polymer, and the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer were measured. The results are shown in Table 3.
[0359] In addition, a polarizing microscope image of a thin sheet-like measurement sample S3 used for measuring the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer is shown in FIG. Figure 8 .
[0360] (Comparative Example 3)
[0361] <Preparation of mixed solid catalyst component>
[0362] A loading container purged with nitrogen was prepared, and 4.7 mg of the solid component (a1) obtained in Production Example 1 and 1.2 mg of the solid component (b1) obtained in Production Example 2 were charged to obtain a mixed solid catalyst component (A3) (solid catalyst component mixture for olefin polymerization).
[0363] Tables 1 and 2 show the content ratios of the respective components in the obtained mixed solid catalyst component (B3).
[0364] <Formation of Polymerization Catalyst and Polymerization Reaction>
[0365] Into a 2.0 liter autoclave equipped with a stirrer and purged with nitrogen were placed 1.32 mmol of triethylaluminum, 0.26 mmol of dicyclopentylbis(ethylamino)silane (T01) and 0.0038 mmol of the mixed solid catalyst component (B3) in terms of titanium atoms to prepare a polymerization catalyst.
[0366] Then, 1.5 liters of hydrogen and 1.4 liters of liquefied propylene were charged, and prepolymerization was carried out at 20°C for 5 minutes. The temperature was then raised and a polymerization reaction was carried out at 70°C for 1 hour.
[0367] The propylene polymerization activity (PP polymerization activity) per 1 g of the solid catalyst component, the melt flowability (MFR) of the polymer, the flexural modulus (FM) of the polymer, and the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer were measured. The results are shown in Table 3.
[0368] In addition, a polarizing microscope image of a thin sheet-like measurement sample S3 used for measuring the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer is shown in FIG. Fig. 9 .
[0369] (Comparative Example 4)
[0370] <Preparation of mixed solid catalyst component>
[0371] A loading container purged with nitrogen was prepared, and 1.6 mg of the solid component (a1) obtained in Production Example 1 and 6.5 mg of the solid component (b1) obtained in Production Example 2 were charged to obtain a mixed solid catalyst component (B4) (solid catalyst component mixture for olefin polymerization).
[0372] Tables 1 and 2 show the content ratios of the respective components in the obtained mixed solid catalyst component (B4).
[0373] <Formation of Polymerization Catalyst and Polymerization Reaction>
[0374] Into a nitrogen-purged, 2.0-liter autoclave equipped with a stirrer were placed 1.32 mmol of triethylaluminum, 0.26 mmol of dicyclopentylbis(ethylamino)silane (T01) and 0.0038 mmol of the mixed solid catalyst component (B4) in terms of titanium atoms to prepare a polymerization catalyst.
[0375] Then, 1.5 liters of hydrogen and 1.4 liters of liquefied propylene were charged, and prepolymerization was carried out at 20°C for 5 minutes. The temperature was then raised and a polymerization reaction was carried out at 70°C for 1 hour.
[0376] The propylene polymerization activity (PP polymerization activity) per 1 g of the solid catalyst component, the melt flowability (MFR) of the polymer, the flexural modulus (FM) of the polymer, and the ratio of the oriented layer in the cross section of the injection molded plate formed from the obtained polymer were measured.
[0377] In addition, a polarizing microscope image of a thin sheet-like measurement sample S3 used for measuring the ratio F (%) of the oriented layer in the cross section of the injection molded plate formed of the obtained polymer is shown in FIG. Fig.10 .
[0378] [Table 1]
[0379]
[0380] [Table 2]
[0381]
[0382] [Table 3]
[0383]
[0384] As can be seen from Table 1 and Table 3, in Examples 1 to 3, a mixture of solid catalyst components for olefin polymerization containing a first solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and a succinic acid diester compound and a second solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and a phthalic acid diester compound is prepared in a manner where the mass ratio of the first solid catalyst component for olefin polymerization: the second solid catalyst component for olefin polymerization = 37:63 to 87:13 is obtained. By using the mixture for olefin polymerization, an olefin polymer having a melt fluidity MFR of up to 80 to 120 g / 10 minutes, excellent formability, a flexural modulus FM of up to 1900 MPa or more, and excellent rigidity can be easily produced.
[0385] This is considered to be because, by subjecting a mixture containing a first olefin polymerization solid catalyst component and a second olefin polymerization solid catalyst component in a predetermined ratio to olefin polymerization, the first olefin polymerization solid catalyst component generates a first olefin polymer having a high bending modulus and a wide molecular weight distribution, and the first olefin polymer having a wide molecular weight distribution shows high compatibility with the second olefin polymer generated using the second olefin polymerization solid catalyst component. Figures 4 to 6 As shown in the ratio F of the oriented layer in Table 3, it can be seen that when olefins are polymerized using the solid catalyst component mixture for olefin polymerization obtained in Examples 1 to 3, the ratio of the oriented layers (Th1 and Th2) that affect the bending modulus in the obtained olefin polymer will not change significantly, and high melt fluidity can be exerted.
[0386] On the other hand, as can be seen from Tables 1 and 3, in Comparative Examples 1 and 2, only one of the solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and succinic diester compound, or the solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and phthalic diester compound was used, and therefore only an olefin polymer having a melt fluidity MFR as low as 56 g / 10 min and poor moldability was obtained (Comparative Example 1), or when used for olefin polymerization, only an olefin polymer having a flexural modulus FM as low as 1720 MPa and poor rigidity was obtained (Comparative Example 2).
[0387] In addition, it can be seen from Table 1 and Table 3 that in Comparative Examples 3 and 4, a mixture of solid catalyst components for olefin polymerization in which the mixing ratio of the first solid catalyst component for olefin polymerization to the second solid catalyst component for olefin polymerization is outside the specified range is prepared and used for olefin polymerization. Therefore, only an olefin polymer with a melt fluidity MFR as low as 78 g / 10 min and poor formability can be obtained (Comparative Example 3), or when used for olefin polymerization, only an olefin polymer with a flexural modulus FM as low as 1780 MPa and poor rigidity can be obtained (Comparative Example 4).
[0388] Industrial Applicability
[0389] According to the present invention, a solid catalyst component mixture for olefin polymerization can be provided, which can easily produce an olefin polymer having both high melt fluidity and rigidity, and a catalyst for olefin polymerization and a method for producing an olefin polymer can be provided.
Claims
1. A solid catalyst component mixture for olefin polymerization, characterized in that: It comprises a first solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and a succinic acid diester compound and a second solid catalyst component for olefin polymerization containing magnesium, titanium, halogen and a phthalic acid diester compound in a manner such that the mass ratio of the first solid catalyst component for olefin polymerization: the second solid catalyst component for olefin polymerization = 37:63 to 87:
13.
2. The solid catalyst component mixture for olefin polymerization according to claim 1, wherein The content of the succinic acid diester compound is 4.7 to 14.9% by mass in terms of solid content.
3. The solid catalyst component mixture for olefin polymerization according to claim 1, wherein The content of the phthalic acid diester compound is 2.2 to 7.9% by mass in terms of solid content.
4. A catalyst for olefin polymerization, characterized in that It contains: (I) the solid catalyst component mixture for olefin polymerization according to claim 1; and (II) one or more organoaluminum compounds selected from the group consisting of compounds represented by the following general formula (1), R 1 p AlQ 3-p (1) In formula (1), R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, p satisfies 0 < p ≤ 3, and when there are multiple R 1 's, each R 1 is optionally the same as or different from each other, and when there are multiple Q's, each Q is optionally the same as or different from each other.
5. The olefin polymerization catalyst according to claim 4, comprising: (I) The solid catalyst component mixture for olefin polymerization according to claim 1; (II) one or more organoaluminum compounds selected from the group consisting of compounds represented by the following general formula (1); and (III) external electron donating compounds, R 1 p AlQ 3-p (1) In formula (1), R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, p satisfies 0 < p ≤ 3. When there are multiple R 1 groups, each R 1 is optionally the same as or different from each other. When there are multiple Q groups, each Q is optionally the same as or different from each other.
6. A method for producing an olefin polymer, characterized in that: Olefins are polymerized using the olefin polymerization catalyst according to claim 4.
7. A method for producing an olefin polymer, characterized in that: Olefins are polymerized using the olefin polymerization catalyst according to claim 5.
Citation Information
Patent Citations
Ingredient and catalyst for olefin polymerization
JP1982063310A
Manufacture of spherical magnesium alkoxide particle
JP1987051633A
Synthesis of spherical magnesium alcoholate having narrow particle size distribution
JP1991074341A
Alkoxy group-containing magnesium compound and production thereof
JP1992368391A
Production of spherical fine particulate magnesium ethylate
JP1996073388A